Faktor Faktor Yang Berhubungan Dengan Kejadian Hiperemesis Gravidarum Pada Ibu Hamil Yang Dirawat Di Bagian Kebidanan Dan Penyakit Kandungan RSUD dr. La Palaloi Maros Periode Tahun 2019-2021 - Hasmawati, Hasmawati HS; Amiruddin, Tedy; Murnita, Ika Azdah (Fakultas Kedokteran Universitas Bosowa, 2024)
Hyperemesis gravidarum is a condition in which pregnant women experience excessive nausea and vomiting that interferes with their health and affects their general condition. The aim of the study was to determine the factors associated with the incidence of hyperemesis gravidarum in pregnant women who were treated at the Department of Obstetrics and Gynecology at RSUD under dr. La Palaloi Maros for the 2019–2021 period. This study's population consisted of pregnant women treated at the RSUD dr. La Palaloi Maros Department of Obstetrics and Gynecology from 2019 to 2021, with a total sample requirement of 166 consisting of 83 cases of hyperemesis gravidarum and 83 controls. The research sample was taken using a simple random sampling technique. This research is a quantitative analytic study with a case-control design approach that uses secondary data in the form of medical records. SPSS software was used to analyze the data, which included the chi-square test and the 95% Odds Ratio Cl test. The results of bivariate data analysis showed that there was a relationship between maternal age and the incidence of hyperemesis gravidarum with a p-value of 0.012 and an OR 2.506 (1.268–4.951). There is a relationship between parity and the incidence of hyperemesis gravidarum with a p-value of 0.002 and an OR of 3.146 (1.547–6.397). There is a relationship between work history and the incidence of hyperemesis gravidarum with a p-value 0.001 and OR 3.160 (1.670-5.978). There is a relationship between educational history and the incidence of hyperemesis gravidarum with a p-value 0.029 and an OR 2.092 (1.123–3.897). The study at dr. La Palaloi Maros concluded that there is a significant relationship between.